15.71% Efficiency All‐Small‐Molecule Organic Solar Cells Based on Low‐Cost Synthesized Donor Molecules. (9th December 2021) - Guo, Jing; Qiu, Beibei; Yang, Dengchen; Zhu, Can; Zhou, Liuyang; Su, Chunjen; Jeng, U‐Ser; Xia, Xinxin; Lu, Xinhui; Meng, Lei; Zhang, Zhanjun; Li, Yongfang
Abstract: Low cost, high efficiency, and high stability are the three key issues of organic solar cells (OSCs) that should be carefully considered to meet the requirement of future commercial applications. Therefore, the development of high‐performance organic photovoltaic materials with low synthetic cost has been becoming a crucial challenge in the field of OSCs. Herein, two new low‐cost small‐molecule donors (SM‐BF1 and SM‐BF2) are designed and synthesized with a facile synthetic route by replacing 4‐bromo‐2‐fluorobenzenethiol and 4‐bromo‐3‐fluorobenzenethiol with low‐cost 4‐bromo‐2‐fluoro‐1‐iodobenzene and 4‐bromo‐3‐fluoro‐1‐iodobenzene as key raw materials. Besides, the influence of the chemical steric effect of the phenyl conjugated side chains of the benzodithiophene (BDT) unit on photophysical properties, charge transfer, and photovoltaic properties are deeply investigated by the modulation of fluorine atom substituted position. As a result, SM‐BF1 with ortho‐fluorinated substituent has outstanding crystallization properties and better miscibility with acceptor Y6 and exhibits more desirable morphology and more balanced charge‐carrier transport properties, leading to a superior power conversion efficiency (PCE) to 15.71%. More encouragingly, according to the figure of merit (FOM) and the industrial figure of merit (i‐FOM) to evaluate the small‐molecule donors, the SM‐BF1‐based device has excellent potential for future commercial applications. Abstract : Two small‐molecule donors, SM‐BF1 and SM‐BF2, are synthesized by a low‐cost synthesis route utilizing cheap raw materials. The champion device based on SM‐BF1:Y6 shows a power conversion efficiency (PCE) of 15.71%, benefitted from its better miscible morphology and more balanced charge‐carrier transport characteristics. Furthermore, through the figure of merit (FOM) analysis, SM‐BF1 also shows a good prospect for commercial application.